Sulfated polysaccharide from Enteromorpha prolifera increases hydrogen sulfide production and attenuates non-alcoholic fatty liver disease in high-fat diet rats. Issue 8 (27th July 2018) - Ren, Rendong; Yang, Zheng; Zhao, Aili; Huang, Yuyang; Lin, Shiying; Gong, Junjie; Chen, Jie; Zhu, Pingping; Huang, Fang; Lin, Wenting
Abstract : EP upregulates hepatic CBS expression, thus increasing serum H2 S level, which reduces serum TG level and ameliorates NAFLD induced by a high-fat diet. Abstract : Enteromorpha prolifera is an edible alga and previous studies have indicated that E. prolifera polysaccharide (EP) attenuates non-alcoholic fatty liver disease (NAFLD) in high-fat diet rats. Hydrogen sulfide (H2 S) has recently been found to exert many physiological effects. The purpose of this study was to evaluate whether EP prevents NAFLD via regulation of H2 S production. EP was orally administered to high-fat diet rats for 5 weeks. Treatment with EP (200 mg per kg body weight per d) significantly increased the serum H2 S level and reduced the serum triglyceride level ( p < 0.05) in rats fed a high-fat diet. These effects were similar to those observed with NaHS, a H2 S donor. Real-time PCR and western blotting analysis revealed that EP significantly upregulated hepatic mRNA and protein expression of cystathionine-β-synthase, which is the enzyme responsible for H2 S production. These results indicate that EP decreases the serum TG level by increasing H2 S production, suggesting that EP may be beneficial for the treatment of NAFLD and may reduce the risk of cardiovascular disease.